Solutions to the Multidimensional Linear Transport Equation by the Spectral Method - M. T. Vilhena, L. B. Barichello, J. R. Zabadal, C. F. Segatto, A. V. Cardona; R. P. Pazos (Progress in Nuclear Energy, 1999)
n/a
n/a